P16 A Systematic Characterisation Of Inflammation In Chronic Thromboembolic Pulmonary Hypertension. (10th November 2014) - Hadinnapola, C; Southwood, M; Jenkins, D; Sheares, K; Toshner, M; Pepke-Zaba, J
Abstract : Introduction: The pathogenesis of chronic thromboembolic pulmonary hypertension (CTEPH) is poorly understood. Idiopathic pulmonary arterial hypertension (IPAH) is associated with systemic and localised inflammation. Distal vasculopathy is seen in IPAH and CTEPH (2 compartment model). Inflammation has also been implicated in CTEPH pathogenesis. We undertook a systematic assessment of inflammatory markers and immune cells to determine the role of inflammation in CTEPH. Methods: We examined the distal tails of 26 pulmonary endarterectomy (PEA) specimens and explanted lungs (5 CTEPH, 11 IPAH). Formalin fixed samples were immunostained with anti-human CD45 (inflammatory cell), CD79a (B cell), CD68 (macrophage) or CD3 (T cell) antibodies. Cell counts were normalised to the area surrounding vessels bounded by airspace structures for perivascular cell counts; to vessel area for media cell counts and per high powered field for lung parenchymal cell counts. Serum was collected from 61 patients pre and 6 months post PEA. Cytokines were measured using a multiplex array (pg/ml; mean±SD). Results: Table 1 . CD3 + cells were less abundant in the media of small vessels (mean 0.03 ± 0.01 mm 2 ) in CTEPH vs. IPAH (p = 0.02). Perivascular and parenchymal cell counts showed non-significant reductions of CD3 + cells in CTPEH (p = 0.19 and 0.08 respectively). More CD68 + cells were seen in the parenchyma in CTEPH (p = 0.03). Few CD20 + cells were seen in parenchyma with no difference. Neovascularisation correlated to CD45 + cells in PEA specimens when normalised to specimen area (r = 0.4, p = 0.01). Conclusions: In CTEPH, most serum cytokines were not elevated sufficiently to suggest systemic inflammation is important in pathogenesis. The change in IL10 and TNFα are possibly due to improvement in cardiac function post PEA as described previously. The relative lack of CD3 + T cells in the media of small arteries in CTEPH suggests that localised inflammation is also less important. The significance of CD68 + cells in CTEPH lung parenchyma needs further assessment. The correlation of CD45 + cells and neovascularisation in PEA specimens may suggest an association between inflammation and neovascularisation. Inflammatory signals maybe related to thrombus remodelling and cardiac dysfunction rather than to CTEPH pathogenesis. Isolating these processes is required to expand on this descriptive study.